THE ROLE OF CANNABINOID RECEPTOR 1 IN DEVELOPMENT OF OXIDATIVE/NITROSATIVE STRESS IN MICE WITH NON-ALCOHOLIC FATTY LIVER DISEASE - Brkić, Dušan N; Jorgačević, Bojan Z (Medicinski podmladak, 2019)
Abstract Introduction: Non-Alcoholic Fatty Liver Disease (NAFLD) is the hepatic manifestation of metabolic syndrome. It represents a spectrum of disease ranging from steatosis,  non-alcoholic steatohepatitis (NASH), that may progress to fibrosis, cirrhosis and eventually hepatocellular carcinoma. Aim: The aim of study was to investigate the influence of cannabinoid receptor subtype 1 (CB1) blockade on intensity of oxidative/nitrosative stress in liver of mice with NAFLD. We therefore used rimonabant, selective CB1 antagonist. Material and methods: Male mice C57BL/6 (n=28) were divided into following groups: 1. Control group - fed with control chow diet 20 weeks (C group; n=7), 2. Group fed with high saturated fat diet 20 weeks (HF group; n=7), 3. Group fed with standard chow diet and treated with rimonabant after 18 weeks (R group; n=7), 4. Group fed with high saturated fat diet and treated with rimonabant after 18 weeks (HFR group; n=7). The activity of liver transaminases was measured in serum. Concentrations of malondialdehyde (MDA), nitrites and nitrates (NOx), including the activity of superoxide dismutase (SOD), copper/zinc superoxide dismutase (Cu/ZnSOD) and manganese superoxide dismutase (MnSOD) were measured in the liver. Results: Rimonabant induced decrease in liver transaminase activity in R group compared to C group (p˂0.01). Similar results were observed in HFR group compared to HF group (p˂0.01). Concentrations of MDA and NOx in HFR were lower compared to control (p˂0.01). We found decrease in  SOD, Cu/ZnSOD and MnSOD activities in HFR group compared to HF group (p˂0.01). Conclusion: According to the results of this study it can be concluded that blockade of CB1 receptors causes useful effects in treatment of NAFLD. Rimonabant reduced hepatocellular injury decreasing the activity of liver transaminases in serum. Reduction of oxidative/nitrosative stress and lipid peroxidation may also contribute to protective effects of rimonabant, shown as decrease in MDA concentration. Keywords: NAFLD, CB1 receptors, endocannabinoid system, rimonabant, oxidative/nitrosative stress